2015
DOI: 10.1016/j.jcomdis.2015.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Overlapping genetic and child-specific nonshared environmental influences on listening comprehension, reading motivation, and reading comprehension

Abstract: This study investigated the genetic and environmental influences on observed associations between listening comprehension, reading motivation, and reading comprehension. Univariate and multivariate quantitative genetic models were conducted in a sample of 284 pairs of twins at a mean age of 9.81 years. Genetic and nonshared environmental factors accounted for statistically significant variance in listening and reading comprehension, and nonshared environmental factors accounted for variance in reading motivati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Therefore, the present findings may not generalize to the relations between other reading cognition and other dimensions of reading motivation. For example, a recent study on a sample of 10-year old U.S. twins used a composite reading motivation score that comprises several different motivation dimensions (i.e., reading self-efficacy, reading curiosity, reading for challenges, reading for recognition, and reading for grades), and found that the concurrent association between reading comprehension and the multidimensional reading motivation was mostly accounted for by nonshared environmental influences (Schenker & Petrill, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the present findings may not generalize to the relations between other reading cognition and other dimensions of reading motivation. For example, a recent study on a sample of 10-year old U.S. twins used a composite reading motivation score that comprises several different motivation dimensions (i.e., reading self-efficacy, reading curiosity, reading for challenges, reading for recognition, and reading for grades), and found that the concurrent association between reading comprehension and the multidimensional reading motivation was mostly accounted for by nonshared environmental influences (Schenker & Petrill, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…Those scholars focused on the relationships between reading level growth rates at different developmental stages and genetic and environmental factors. Furthermore, Schenker and Petrill ( 2015 ) employed both univariate and multivariate quantitative genetic models to measure data obtained from 284 pairs of children with an average age of 9.81 years. Their study found a strong correlation between reading motivation and reading ability in the presence of non-shared environmental factors.…”
Section: Resultsmentioning
confidence: 99%
“…Another study was conducted by Schenker & Petrill (2015) to examine the genetic and environmental influences on observed associations between listening comprehension, reading motivation, and reading comprehension. The findings of the study indicated that both of listening and reading comprehension appear to be primarily related due to genetic factors whereas motivation appears to affect reading via childspecific, no shared environmental effects.…”
Section: Additionally Hogan and Et Al (2014) Conducted A Research To ...mentioning
confidence: 99%